Attention Deficit Hyperactivity Disorder and Medication Use by Children During Parental Military Deployments. Issue 5 (1st May 2014) - Hisle-Gorman, Elizabeth; Eide, Matilda; Coll, Edward J.; Gorman, Gregory H.
ABSTRACT: Objective: Parental deployment is associated with children's increased mental health needs. Attention Deficit Hyperactivity Disorder (ADHD) is the most common pediatric mental health diagnosis. We hypothesize children with ADHD will have increased mental health and medication needs during parental deployment. Methods: Retrospective cohort study of children with ADHD aged 4–8 years in the Military Health System. Results: Of 413, 665 children aged 4–8 years, 34, 205 (8.3%) had ADHD and 19, 123 (55.9%) of these were prescribed ADHD medications. During parental deployments, children with ADHD had a 13% increased rate of mental and behavioral health care visits (IRR 1.13 [95% CI 1.12–1.14; p < 0.00001]) and a decreased rate of medication changes (IRR 0.94 [95% CI 0.91–0.96; p < 0.00001]) compared to when parents were at home. Medication changes related to deployment varied by age; school-aged children had decreased medication events (IRR 0.88 [95% CI 0.86–0.91; p < 0.00001]) and preschool-aged children had increased medication events (IRR 1.05 [95% CI 1.02–1.10; p =.006]) during parental deployment. Conclusions: During parental deployment, children with ADHD aged 4–8 years have increased mental health visits and decreased ADHD medication changes. Younger children have increased medication changes, whereas older children have decreased changes during a parent's deployment.